Power: the Darwin college lectures - Blackwell,Alan (ed.); Mackay, David (ed.) (New York, 2005)
In this book, first published in 2006, seven internationally renowned writers address the theme of Power from the perspective of their own disciplines. Energy expert Mary Archer begins with an exploration of the power sources of our future. Astronomer Neil Tyson leads a tour of the orders of magnitude in the cosmos. Mathematician and inventor of the Game of Life John Conway demonstrates the power of simple ideas in mathematics. Screenwriter Maureen Thomas explains the mechanisms of narrative power in the media of film and videogames, Elisabeth Bronfen the emotional power carried by representations of life and death, and Derek Scott the power of patriotic music and the mysterious Mozart effect. Finally, celebrated parliamentarian Tony Benn critically assesses the reality of power and democracy in society.
Keywords: Power